Liquid Drops Hurdling Barriers of Various Geometries. Issue 17 (10th July 2017) - Jiang, Xiaofeng; Li, Huai Z.
Abstract : Drop manipulation and mobility on a solid surface has received widespread attention. However, how a soft liquid drop interacts with a barrier in the direction of its motion, this question still remains open. This study shows liquid drop hurdling the preconditioned barriers with various geometries displaying superhydrophobic surface. Unlike human being, they cannot anticipate barriers and the only possibility is just head‐on confrontation, by deforming themselves to adapt to the barrier's geometry. This study demonstrates experimentally that both the external factors like barriers' geometry and size and internal factors such as drops' initial motion velocity, volume, surface tension, and dynamic viscosity can affect their hurdling dynamics. The hurdling difficulty is quantified through the time and energy loss. These observations throw insight into the dynamics of liquid drops moving on a solid obstacle‐equipped surface, which may facilitate the potential applications like coating technology and liquid transportation. Abstract : The dynamical behavior of liquid drops hurdling different barriers exhibiting superhydrophobic properties is experimentally investigated under various conditions, including noticeable drops' nature and barriers' geometry. Both the external factors (like barriers' geometry and size) and internal factors (drops' initial motion velocity, volume, surface tension, and viscosity) can affect the drops' hurdling process. The square barrier is the most laborious geometry for drops to hurdle while the semicircle is the most advantageous. The hurdling difficulty is quantified through the time and energy consuming.